Nationalist China on Taiwan and the Cold War, 1958-1971: the struggle for stability and status - So, N (2019)
This thesis studies the diplomatic behaviours of Nationalist China on Taiwan in the period from 1958-1971. It examines the decision-making process over the episodes including the 1958 Taiwan Strait Crisis; the Chinese representation debate in the United Nations in 1961; the façade of a military crisis in 1962; the involvement in the Vietnam War from 1964-1966; and the withdrawal from the United Nations in 1971. It addresses questions including: what were the calculations and motivations of Nationalist China’s officials when dealing with those episodes? How far was policy formulation shaped by their understanding of the domestic political dynamics and the international circumstances? To what extent were the behaviours of Nationalist China relevant to the Cold War? And how influential was the Cold War as a factor on decision-making? These questions are the lenses from which we make sense of the trajectory in which Nationalist China’s leaders struggled for consolidating their political status and attaining the state of stability.